Tren Baru Kosmetik "Share in Jar" Ilegal di Media Daring - Iin Febrianti Sende; Edi Priyo Yunianto (Eruditio : Indonesia Journal of Food and Drug Safety, 2020)
The Effect of Cosmetic formula on the skin is one of the main reasons for the new consumer to buy cosmetics. Before buy, new consumers feel confused about whether the cosmetic product is suitable for their skin or not. They need product tester. Unfortunately, not every cosmetic product sold in the market has a tester size. This condition led to the emergence of new illegal cosmetics trends in online media, namely share in jar. The concept of "share in a jar" is to divide (share) the content of the cosmetic product in (in) several small packaging (jar), with the aim that someone can buy and try the cosmetic product without buying the product in its original size. The study was conducted by online mapping and Google Trends analysis to review the phenomenon of cosmetics share in jar in online media, and also literature study of crime prevention strategies to provide intervention options that can be used. The results show that share in jar cosmetics are sold through various e-commerce and social media, and based on Google Trends analysis, the level of share in jar search has increased in the last 3,5 years. Most of them are import cosmetics in relatively high prices, and the most category is skincare cosmetics. Crime prevention strategies that can be done are through social crime prevention, situational crime prevention, and community-based crime prevention approaches, by intervening factors that influence cosmetics share in the jar distribution.